2016
DOI: 10.1002/casp.2278
|View full text |Cite
|
Sign up to set email alerts
|

Is Group Singing Special? Health, Well‐Being and Social Bonds in Community‐Based Adult Education Classes

Abstract: Evidence demonstrates that group singing improves health and well-being, but the precise mechanisms remain unknown. Given that cohesive social networks also positively influence health, we focus on the social aspects of singing, exploring whether improvements in health and well-being are mediated by stronger social bonds, both to the group as a whole (collectivebonding) and to individual classmates (relational-bonding). To do so, seven newly-formed community-based adult education classes (four singing, N=84, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 50 publications
(78 reference statements)
2
39
1
2
Order By: Relevance
“…Indeed, recent research into arts participation has shown that engaging in the arts within a group provides greater psychological benefits than engaging in arts activities alone (Stewart & Lonsdale, ; Weinberg & Joseph, ). Moreover, Pearce, Launay, Machin, and Dunbar () found that collective bonding within community ABGs predicted improvements in participants’ psychological flourishing and anxiety. However, even though research suggests that social connectedness and support is a key benefit to participating in ABGs, few studies have examined how social connectedness in ABGs improves mental wellbeing among people with CMHC (Van Lith, Schofield & Fenner, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent research into arts participation has shown that engaging in the arts within a group provides greater psychological benefits than engaging in arts activities alone (Stewart & Lonsdale, ; Weinberg & Joseph, ). Moreover, Pearce, Launay, Machin, and Dunbar () found that collective bonding within community ABGs predicted improvements in participants’ psychological flourishing and anxiety. However, even though research suggests that social connectedness and support is a key benefit to participating in ABGs, few studies have examined how social connectedness in ABGs improves mental wellbeing among people with CMHC (Van Lith, Schofield & Fenner, ).…”
Section: Introductionmentioning
confidence: 99%
“…No studies have yet examined social identification to ABGs in the context of CMHC. However, a recent study among community members found that the extent to which participants experienced collective bonding in singing, creative writing or crafts groups predicted benefits to health and wellbeing (Pearce et al, ). Therefore, the second hypothesis predicted that, over time, greater mental wellbeing increases should be observed when participants identified more strongly with the ABG (H2).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced self-care, personal growth and building social connections was found from community pottery (Genoe and Liechty 2017), and artists (Reynolds 2009), knitters (Riley et al 2013), quilters (Dickie 2011) and members of singing groups (Clift et al 2010;Judd and Pooley 2014) all experienced benefits of relaxation, stress relief, creativity, feelings of happiness, and higher cognitive function. For social interaction, group knitting (Riley et al 2013) and group singing (Pearce et al 2016) both helped enhance social contact and forge social bonds. Art and craft activities helped retired older adults regain occupational identity (Howie et al 2004) and pleasure and purpose (Liddle et al 2013).…”
mentioning
confidence: 99%
“…Some research has begun to directly contrast different creative activities. Pearce and colleagues compared newly-formed singing, creative writing and crafting groups, finding more rapid social bonding in the music group (Pearce et al 2015) but no group differences after 7 months on wellbeing measures (Pearce et al 2016). Johnson et al (2017) found higher levels of physical (but not psychological) quality of life in older adult choir singers compared to other older adults, including those involved in other hobbies.…”
mentioning
confidence: 99%
See 1 more Smart Citation